Keeping essential reproductive, maternal and child health services available during COVID-19 in Kenya, Mozambique, Uganda and Zimbabwe: analysis of early-pandemic policy guidelines - Marya K. Plotkin; Katie M. Williams; Absolom Mbinda; Vivaldo Nunes Oficiano; Benard Nyauchi; Patrick Walugembe; Emily Keyes; Barbara Rawlins; Donna McCarraher; Otto N. Chabikuli (BMC, 2022)
Abstract Background The COVID-19 pandemic has disrupted the provision of essential reproductive, maternal, newborn, and child health (RMNCH) services in sub-Saharan Africa to varying degrees. Original models estimated as many as 1,157,000 additional child and 56,700 maternal deaths globally due to health service interruptions. To reduce potential impacts to populations related to RMNCH service delivery, national governments in Kenya, Mozambique, Uganda, and Zimbabwe swiftly issued policy guidelines related to essential RMNCH services during COVID-19. The World Health Organization (WHO) issued recommendations to guide countries in preserving essential health services by June of 2020. Methods We reviewed and extracted content related to family planning (FP), antenatal care (ANC), intrapartum and postpartum care and immunization in national policies from Kenya, Uganda, Mozambique, and Zimbabwe from March 2020 to February 2021, related to continuation of essential RMNCH services during the COVID-19 pandemic. Using a standardized tool, two to three analysts independently extracted content, and in-country experts reviewed outputs to verify observations. Findings were entered into NVivo software and categorized using pre-defined themes and codes. The content of each national policy guideline was compared to WHO guidance related to RMNCH essential services during COVID-19. Results All four country policy guidelines considered ANC, intrapartum care, FP, and immunization to be essential services and issued policy guidance for continuation of these services. Guidelines were issued in April 2020 by Mozambique, Kenya, and Uganda, and in June 2020 by Zimbabwe. Many elements of WHO's 2020 recommendations were included in country policies, with some notable exceptions. Each policy guideline was more detailed in some aspects than others - for example, Kenya's guidelines were particularly detailed regarding FP service provision, while Uganda's guidelines were explicit about immediate breastfeeding. All policy guidance documents contained a balance of measures to preserve essential RMNCH services while reducing COVID-19 transmission risk within these services. Conclusions The national policy guidelines to preserve essential RMNCH services in these four countries reflected WHO recommendations, with some notable exceptions for ANC and birth companionship. Ongoing revision of country policy guidelines to adapt to changing pandemic conditions is recommended, as is further analysis of subnational-level policies.